Importance of Writing Skills in ESP Classes - Gulomovna, Yakubova Lobar (Researchparks Publishing, 2023)
In teaching and learning any languages, writing is essential to acquire a language in written form. However, writing skill require a lot of knowledge and experience from the learners to express their thoughts towards specialty. Therefore, FL learners fundamentally should have knowledge in grammar, phonetics and vocabulary. Furthermore, we conducted research with the adult learners who study at the faculty of oil and gas engineering on the issues concerning increasing writing skills.